Penerapan Akad Murabahah pada Layanan Kredit di Bank Perekonomian Rakyat Syariah (BPRS) Niaga Madani Kota Makasar - Nur Ifnah; Muhtasib; Anisa Nurfayda (CV. Creative Tugu Pena, 2024)
Sharia banking is currently on the rise and has become a reference for the public, one of which is in carrying out financing using a profit sharing system. Therefore, various sharia banking products must be able to be understood by the public, one of which is the implementation of the murabahah contract at PT. BPRS Niaga Madani, Makassar city. The aim of this research is to determine the application of the murabahah contract in credit services at Bank Per Ekonomi Rakyat Syariahl (BPRS) Niaga Madani, Makasar City. This research is qualitative research using a phenomenological approach. The data collection methods used in line research are observation, interviews, and documentation. The data obtained is then analyzed qualitatively, namely by organizing the data, breaking it down into units, synthesizing it, arranging it into patterns, choosing what is important and what will be studied so that a conclusion can be made to be conveyed to others. The research results show that the implementation of Murabahah financing at PT. BPRSlNiaga Madani Makassar city starts from applying for financing, collecting the necessary documents and validating guarantees from prospective customers as well as carrying out surveys by visiting the prospective customer's home or business location directly. PT. BPRS Niaga Madani Makassar city in implementing marabahah contract financing uses the principle of prudence in providing murabahah financing in the form of 5 Cs, namely Character (character), Capacity (ability), Capital (capital), Collateral (collateral), Condition Of Economic (economic conditions) . Apart from that, in resolving problematic customer disputes in murabahah financing, PT. BPRS Niaga Madani Makassar city resolved it by deliberation and peacemaking (sulhu).